Il De gemitu Columbae del cardinale Roberto Bellarmino e lo jus publicum ecclesiasticum (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa - 2. Rilevanza del De gemitu per una “teologia politica” - 3. Il problema dell’appartenenza all’Ecclesia: il canto della “Colomba” - 4. Il can. I della Distinctio XCII del Decretum di Graziano - 5. Osservazioni conclusive.De gemitu Columbae by Cardinal Roberto Bellarmino and the jus publicum ecclesiasticumABSTRACT: One of the minor works of cardinal Roberto Bellarmino, De Gemitu Columbae sive De Bono lacrymarum (1617) is composed of three books: the first is dedicated to the "need for moans"; the second and third, respectively, to the sources and the fruits of the "tears". In investigating the origin of the moan, after quoting Isaiah and Nahum, the Author insists on a verse, particularly evocative, taken from the Song of Songs (6, 9). Therefore, the moan is not referred only to the animal in itself, but also to the whole Church: the work in question seems to be more connected to the textures of a "political theology" than to the classic counter-reformed edification readings. The present contribution aims to examine the relationships between De gemitu and the jus publicum ecclesiasticum, not only externum but also - and above all - internum. And, by this way, the highly debated theme of belonging to the Ecclesia, faced by the great Counter-reform theorist through the images of the dove and the chant.